(untitled) (Research, Society and Development, 2020)
The objective of the study isidentify the practices that nurses can use to prevent childhood obesity. It is an integrative literature review with articles published in the Portuguese language using the indexed descriptors for childhood obesity, nursing and prevention through searches in the SCIELO, LILACS and BDENF databases. To define the guiding question, the PICO strategy was used and in relation to the study selection process, the PRISMA flowchart was explained. The searches for the articles covered the periods from 2014 to 2020, where the articles available in Portuguese, in full and in the original format, were selected. Thus, 8 articles were selected for analysis through the narrative synthesis, based on the inclusion and exclusion criteria. It was found the importance of nursing in the prevention of childhood obesity, since these professionals can work in different areas of society, always prioritizing health and education through guidelines on the importance of healthy eating, the practice of physical exercises, among other factors that contribute to the prevention of obesity, also computerizing the importance of the family in the face of the situation. Therefore, the nursing team has an essential role in the identification and prevention of childhood obesity, which is why, this professional has a versatility of action when it comes to prevention.